Intrauterine Inflammation Alters the Transcriptome and Metabolome in Placenta - Lien, Yu-Chin; Zhang, Zhe; Barila, Guillermo; Green-Brown, Amy; Elovitz, Michal A.; Simmons, Rebecca A. (Frontiers in Physiology, 2020)
Placental insufficiency is implicated in intrauterine infection-associated spontaneous preterm birth (SPTB). We hypothesized that intrauterine inflammation leads to deficits in the capacity of the placenta to maintain bioenergetic and metabolic stability during pregnancy ultimately resulting in SPTB. Using a mouse model of intrauterine inflammation that leads to preterm delivery, we performed RNA-seq and metabolomics studies to assess the association of LPS-induced inflammation and the alterations of gene expression and metabolites in placenta. 1871 differentially expressed genes were identified in LPS-treated placenta. Among them, 1149 and 722 transcripts were increased and decreased, respectively. Ingenuity pathway analysis showed alterations in genes and canonical pathways critical for regulating oxidative stress, mitochondrial function, and metabolisms of glucose and lipids in LPS-treated placenta. Many upstream regulators and master regulators important for nutrient-sensing and mitochondrial function were also altered in LPS-treated placenta, including STAT1, HIF1α, mTOR, AMPK, and PPARα. Comprehensive quantification of metabolites demonstrated significant alterations in the glucose utilization, metabolisms of branched-chain amino acids, lipids, purine and pyrimidine, as well as carbon flow in TCA cycle in LPS-treated placenta compared to control placenta. Collectively, significant and biologically relevant alterations in the placenta transcriptome and metabolome were identified in LPS-treated mice. Altered mitochondrial function and energy metabolisms may underline the mechanisms of inflammation-induced placental dysfunction.